Religious Practice and Student Performance: Evidence from Ramadan Fasting - Erik Hornung; Guido Schwerdt; Maurizio Strazzeri (Center for Economic Studies and ifo Institute (CESifo), 2021)
We investigate how the intensity of Ramadan affects educational outcomes by exploiting spatio-temporal variation in annual fasting hours. Longer fasting hours are related to increases in student performance in a panel of TIMMS test scores (1995–2019) across Muslim countries but not other countries. Results are confirmed in a panel of PISA test scores (2003–2018) allowing within country-wave comparisons of Muslim to non-Muslim students across Europe. We provide evidence consistent with the hypothesis that a demanding Ramadan during adolescence affects educational performance by facilitating formation of social capital and social identity via increased religious participation and shared experiences among students.
Keywords: I21; Z12; J24; O15; 330; education; religion; religious participation; Ramadan; social identity; social capital; PISA; TIMMS